Conservative Surgical Management of Postpartum Hemorrhage (PPH) Using ’Surabaya Method’ (Modified B-Lynch Compression Suture) - Agus Sulistyono (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To evaluate the efficacy of PPH management by conservative surgical management using B-Lynch Method and Surabaya method (Modified B-Lynch compression suture) as an alternative to hysterectomy in PPH due to uterine atony. Method: Eighty-four cases of PPH from 2786 deliveries were recruited in period of July 1, 2007 - August 31, 2008. The study was perfomed in Ob/Gyn Dept. Dr. Soetomo Hospital Surabaya, Indonesia. Its management consisted of 72 cases succeed with medical (uterotonics) and mechanical technique (tamponade technique) and the remain of 12 failed cases was done by conservative surgical technique that preserving uterus. The surgically therapy on these 12 cases were proceeded by B-Lynch technique on 4 cases and another 8 cases with Surabaya Method in which the technique was done by performing brace suturing way with 3 longitudinally stitches using chromic catgut no 2 and round needle. Result: From 12 cases showed that all 8 cases with Surabaya Method technique were success to stop bleeding, but 2 cases were failed from B-Lynch Method and hysterectomy were done. Two out of 8 cases Surabaya Method and 1 B-Lynch technique case were ended with death which possible causes were HELLP syndrome, DIC and multiple organ failure complication in severe preeclampsia, although actually the bleeding had already been stopped. Conclusion: The present study showed that Surabaya Method was effective to stop bleeding in PPH conservative surgical management with uterus preserving. Beside simple, effective and easy to implement, the advantage of Surabaya Method was quick. [Indones J Obstet Gynecol 2010; 34-3: 108-13] Keywords: PPH conservative management, Surabaya Method, B-Lynch technique